Fractional Parts in 2019

Calculus Level 5

0 1 ( { 1 x } { 2 x } ) d x x \displaystyle \int_{0}^{1}{\left(\left\{ \frac{1}{x}\right\} \{ 2x \}\right) \frac{dx}{x} }

The above integral is equal to A + ln B C γ , A+\ln{B}-C\gamma, where A , B , C A,B,C are all positive integers.

Find A + B + C . A+B+C.

Note : { } \{ \} denotes the fractional part and γ \gamma denotes the Euler-Mascheroni constant.


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jan 4, 2019

First note that 0 1 { 1 x } { 2 x } d x x = 0 1 2 { 1 x } 2 x d x x + 1 2 1 { 1 x } ( 2 x 1 ) d x x = 2 0 1 { 1 x } d x 1 2 1 { 1 x } d x x \int_0^1 \left\{\tfrac{1}{x}\right\} \,\left\{2x\right\}\,\frac{dx}{x} \; = \; \int_0^{\frac12} \left\{\tfrac{1}{x}\right\} \,2x\,\frac{dx}{x} + \int_{\frac12}^1 \left\{\tfrac{1}{x}\right\} \,(2x-1)\,\frac{dx}{x} \; = \; 2\int_0^1 \left\{\tfrac{1}{x}\right\}\,dx - \int_{\frac12}^1 \left\{\tfrac{1}{x}\right\} \,\frac{dx}{x} and 1 N + 1 1 { 1 x } d x = n = 1 N 1 n + 1 1 n { 1 x } d x = n = 1 N 1 n + 1 1 n ( 1 x n ) d x = 1 N + 1 1 d x x n = 1 N n ( 1 n 1 n + 1 ) = ln ( N + 1 ) H N + 1 + 1 \int_{\frac{1}{N+1}}^1 \left\{\tfrac{1}{x}\right\}\,dx \; = \; \sum_{n=1}^N \int_{\frac{1}{n+1}}^{\frac{1}{n}}\left\{\tfrac{1}{x}\right\}\,dx \; = \; \sum_{n=1}^N \int_{\frac{1}{n+1}}^{\frac{1}{n}}\left(\tfrac{1}{x} - n\right)\,dx \; = \; \int_{\frac{1}{N+1}}^1 \frac{dx}{x} - \sum_{n=1}^N n\left(\frac{1}{n}- \frac{1}{n+1}\right) \; = \; \ln(N+1) - H_{N+1} + 1 for any N N N \in \mathbb{N} . Letting N N \to \infty gives 0 1 { 1 x } d x x = 1 γ \int_0^1 \left\{\tfrac{1}{x}\right\}\,\frac{dx}{x} \; = \; 1 - \gamma Since 1 2 1 { 1 x } d x x = 1 2 1 ( 1 x 1 ) d x x = 1 ln 2 \int_{\frac12}^1 \left\{\tfrac{1}{x}\right\}\,\frac{dx}{x} \; = \; \int_{\frac12}^1 \left(\tfrac{1}{x}-1\right)\,\frac{dx}{x} \; = \; 1 - \ln2 we deduce that 0 1 { 1 x } { 2 x } d x x = 2 ( 1 γ ) ( 1 ln 2 ) = 1 + ln 2 2 γ \int_0^1 \left\{\tfrac{1}{x}\right\} \,\left\{2x\right\}\,\frac{dx}{x} \; = \; 2(1-\gamma) - (1 - \ln2) \; = \; 1 + \ln2 - 2\gamma making the answer 1 + 2 + 2 = 5 1 + 2 + 2 = \boxed{5} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...